The International Entry Choices of Italian SMEs in Emerging Markets: a Case-based Analysis - Cannavale, Chiara; Laurenza, Elena (Ekonomika, 2018)
The paper addresses the factors influencing the SMEs’ entry choices in international markets and explores two factors: one related to the external environment and one dependent on firms. The first factor is the institutional context as the whole of formal and informal rules of the country target. The second is the market commitment, intended as resources committed in a particular market area: the experience firms get in foreign markets and a general attitude to maintain the international presence for a long period are the main sources of market knowledge. The aim of the study is to understand the effect of company-specific factors and of context-specific factors, namely the market commitment and institutional context, on SMEs’ entry choice mode in foreign markets. The paper develops a multiple case study analysis of four small international Italian firms. Built on the institutional theory and on the market commitment construct, the paper offers a conceptual model that shows that the institutional context strongly influences the amount of resources involved in the internationalization process, while the market commitment affects more the complexity – and intensity – of the process.